2020
DOI: 10.1097/mnm.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of 18F-2-fluoro-2-deoxy-D-glucose PET/computerized tomography in identifying bone marrow infiltration in new patients with diffuse large B-cell lymphoma and Hodgkin lymphoma

Abstract: Objective To compare between 18F-2-fluoro-2-deoxy-D-glucose PET/computerized tomography (18F-FDG PET/CT) and routine iliac bone marrow biopsy (BMB) in assessment of bone marrow infiltration (BMI) in Hodgkin lymphoma and diffuse large B-cell lymphoma (DLBCL) patients at initial presentation. Patients and methods A retrospective analysis of 138 patients (50 Hodgkin lymphomas, 88 DLBCLs). The study included 70 males and 68 females with median age of 43 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
3
4
0
Order By: Relevance
“…However, the diagnostic performance of BMB is better in NHL than in HL. These results are consistent with those reported by Kandeel et al, who revealed that 18 F-FDG PET/CT demonstrated better diagnostic accuracy than BMB in detecting BMI in patients with HL (Kandeel et al 2020 ). .…”
Section: Discussionsupporting
confidence: 92%
“…However, the diagnostic performance of BMB is better in NHL than in HL. These results are consistent with those reported by Kandeel et al, who revealed that 18 F-FDG PET/CT demonstrated better diagnostic accuracy than BMB in detecting BMI in patients with HL (Kandeel et al 2020 ). .…”
Section: Discussionsupporting
confidence: 92%
“…It seems that PET sensitivity is higher when BM is focal rather than diffuse [ 10 ], which indicates that some studies considered true positive cases for BMi those with PET+ by a focal pattern [ 16 , 33 , 44 ]. Studies that used a true positive BMi defined by BMB+ or by PET+ if accompanied with targeted/morphologic imaging changes or FDG disappearance with response after treatment or concordant FDG progression on follow-up [ 10 , 44 , 46 ], reported a higher PET sensitivity and diagnostic accuracy, while a higher BMB specificity. Equivalent findings were seen in one study that considered BMB+ or PET+ focal as true positive BMi [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the BM uptake pattern by PET, three studies reported the prognostic significance of PET+ focal [ 20 , 46 , 48 ]. Chen et al presented data about prognosis according to focal and diffuse PET+ patterns, showing PET+ focal cases had a worse impact in both EFS and OS, while PET+ diffuse cases did not relate to a worse outcome.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review involved some limitations. In some studies PET/CT images were interpreted using qualitative criteria [15][16][17]19,20,22,26,29,31,[34][35][36][37][38][39]42,43,47,48,50,[52][53][54], whereas in other studies both qualitative and quantitative criteria were used [18,21,[23][24][25]27,28,30,32,33,40,41,[44][45][46]49,51,55]. As the qualitative evaluation is based on a subject's experience, this might underestimate the PET/CT diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%